GAMBARAN PENGETAHUAN, SIKAP, HYGIENE PERSONAL DAN PENGGUNAAN AC DENGAN KEJADIAN HAND FOOT MOUTH DISEASES (HFMD) DI KOTA PONTIANAK TAHUN 2024 - Fahrul Alam; Selviana; Ufi Ruhama; Helfi Nolia (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Hand, foot, and mouth disease (HFMD) or known as foot, hand and mouth disease is one of the acute viral infectious diseases caused by coxsackievirus A type 16 (CV A16) and enterovirus 71 (E71) which is usually mild and goes away on its own. Although the disease is mild and can heal itself, this disease is very contagious so it has the potential to become an extraordinary event (KLB). In Pontianak City, there were 83 confirmed cases recorded at the Pontianak City Health Office. The type of research used in this study is descriptive research which aims to obtain a picture of Knowledge, Attitudes, Personal Hygiene and Use of AC with the Incident of Hand Foot Mouth Diseases (HFMD) in Pontianak City in 2024. The sample in this study was 67 children who were confirmed to have Singapore flu in Pontianak City. The results of the study showed that most children aged <5 years were (68.7%), female (52.2%), children who had not attended school (55.2%), maternal education up to high school and college (46.3%), children's bedrooms using air conditioning (AC) (68.7%), good maternal knowledge (56.7%), supportive maternal attitudes (53.7%), and good personal hygiene (55.2%). From the results obtained, the suggestions that can be given are expected for health workers to continue to improve the recording and search for cases of Foot and Mouth Disease (HFMD) in Pontianak City.